Kemandirian Belajar Ditinjau dari Dukungan Sosial Orangtua pada Siswa Sekolah Menengah Atas - Pardosi, Nicolas; Atrizka, Diny (ANALITIKA, 2018)
This study aimed to determine the relationship between parental social support and self regulated learning. The hypotesis proposed that there was a positive relationship between parental social support and self regulated learning, assuming that the higher parental social support, the higher the self regulated learning and vice versa. The research subjects in this study were 147 students of class X-XI Padang Bulan GKPI Senior High School in Medan. Data was obtained from a scale to measure parental social support and self regulated learning. The calculation was carried out through an analysis prerequisite test (assumption test) which consists of normality test and linearity test. Data was analyzed by using Product Person Moment correlation through SPSS 17 for Windows. The results of the data analysis showed a correlation coefficient of 0.572 with p of 0.000 (p <0.005). This result showed that there was a positive relationship between parental social support and self regulated learning. Based on the result, it can be concluded that there was a positive relationship between parental social support and self regulated learning. In the other words, the hypothesis was accepted.